The influence of mental health and a-riseba shooting practice on the performance of basketball shooting results in 16-18 years age group - Aris Mulyono; Nofi Marlina Siregar; Iman Sulaiman (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective; testing the influence and differences in the effects of conventional A-riseba training (A1), A-riseba training with the involvement of parents and people closest to them during the exercise (A2), A-riseba training with the provision of Self-Manage Mental Health literacy during the exercise (A3) on the shooting performance of basketball athletes for players who are or are experiencing; anxiety (B1), eating disorders/disordered (B2), stress (B3), burnout (B4), kinesiophobia (B5), attention-deficit/hyperactivity disorder (B6). Method: The research employed an experimental method with a 3x6 factorial design where treatment was needed, the sampling technique used stratified random sampling so that 72 basketball athletes were selected. The Stroop Test is used to classify mental health disorders, measuring shooting performance using the Basketball Skills Test and BJSAT. Hypothesis testing uses Paired-samples t tests and Two way Anova. Results: There is an influence of A1 [t-count-12.301>t-table1.174, Sig.0.000<p0.05], A2 [t-count-12.988>t-table1.174, Sig.0.000<p0.05], and A3 [t-count-12.245>t-table1.174, Sig.0.000<p0.05] on improving the shooting performance of basketball athletes. There was no difference in the influence of A1, A2, and A3 on the shooting performance of B1, B2, B3, B4, B5, and B6 [P>0.05]. There was a significant gap between B1, B2, B3, B4, B5, and B6 (P<0.05), and there was an interaction between groups (A and B) (P<0.05). The effects of different mental health disorders produce different shooting performance. The Researchers recommend that optimal efforts should be carried out comprehensively, because it has been proven that efforts carried out separately do not have a significant difference in effect.